Comparison of Suprachoroidal Injection of Triamcinolone Acetonide Versus Intravitreal Bevacizumab in Primary Diabetic Macular Odema - Faisal Anwar, Asad Aslam Khan, Tehseen Mahmood Majhu, Rana Mohammad Mohsin Javaid, Muhammad Tahir Ghaffar, Mohammad Hasan Bokhari (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Present study aims to compare the efficacy of single dose triamcinolone acetonide suspension in suprachoroidal space and intravitreal bevacizumab in primary diabetic macular edema patients. Study design: Prospective observational study Study duration and settings: Study was conducted at department of ophthalmology, Eye Unit III, Mayo hospital Lahore (KEMU) from March 2020 to August 2020. Material and methods: The WHO calculator was used to estimate a sample size of 136 patients (66 patients in each group). Non-probability sequential sampling was used to identify patients.. Intravitreal bevacizumab injections (2.5 mg/0.1 mL) were given to patients in Group A, and triamcinolone acetonide was given to patients in Group B, all at random. After one and three months, patients were reassessed. Results: Total 135 patients were included in study. There were 71(52.2%) male and 65(47.8%) female. Mean age of patients was 41.1±6.9SD. BCVA improved 5 letters after 3 month was significantly high in TA group as compared to IVB (P=0.002). Moreover, CSF decreased at least 10% from baseline after one and three months was comparatively high in TA group (p=0.01 and p=0.04 respectively). Among all the patients in IVB group, 29.5% showed efficacy while in group TA, 37.5% showed efficacy (p=0.03) Conclusion: Triamcinolone acetonide is an efficient drug for management of diabetic macular edema. Triamcinolone had long standing effect as compared to intravitreal bevacizumab on structural and functional outcome of the patients with primary diabetic macular odema. Both interventions are associated with limited complications.